Analisis Laporan Keuangan Untuk Memprediksi Tingkat Kebangkrutan Dengan Menggunakan Model Altman Z- Score, Grover dan Zmijewski - Dian Dwi Sahniar; Tatas Ridho Nugroho; Nurdiana Fitri Isnaini; Imam Baidlowi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze financial statements to determine the potential for bankruptcy in companies in the transportation and logistics sector using the Altman Z-score, Grover and Zmijewski methods. The research used is quantitative with a descriptive approach. The population used is 28 companies in the transportation and logistics sector. The sample used in this research was 15 companies using purposive sampling technique in taking the sample. Statistical analysis in this study uses the calculation of the company's financial ratios from each bankruptcy method. The data used is secondary data in the form of financial reports obtained from the Indonesian Stock Exchange. The results showed that of the 15 sample companies using the Altman method, 8 were bankrupt, 1 was a gray area, 6 were healthy. Grover's results are 7 bankrupt and 8 healthy and Zmijewski's results are 10 bankrupt, 5 healthy. And of the 15 sample companies, there are 5 companies that have a greater potential for bankruptcy using these three methods.